Magnetic Engine Magnetic head to head collision repulsive piston engine (MHCRPE) (International Journal of Engineering and Computer Science, 2017)
Now a days, we are using bike, car, bus, etc for transportation. As we known petrol or diesel required to run them. Mainly those fuels are from natural resources, so we have been using those fuels exclusively. Now it is at the stage of extinction. The combustion of those fuels caused global warming, which in turn affected the earth atmosphere and weather. In order to overcome those problems we required an energy efficient fuel or engine. Hence I developed a magnetic engine, that will operate without any fuels such as petrol, diesel, even bio-fuel. And it is energy efficient. It is not producing any harmful gases, because of there is no any combustion takes place in the engine.